Arithmetic Errors in Financial Contexts in Parkinson’s Disease - Loenneker, Hannah D.; Becker, Sara; Nussbaum, Susanne; Nuerk, Hans-Christoph; Liepelt-Scarfone, Inga (Frontiers in Psychology, 2021)
Research on dyscalculia in neurodegenerative diseases is still scarce, despite its high impact on patients’ independence and activities of daily living function. Most studies address Alzheimer’s Disease; however, patients with Parkinson’s Disease (PD) also have a higher risk for cognitive impairment, while its relation to arithmetic deficits in financial contexts has rarely been studied. Therefore, the current exploratory study investigates deficits in two simple arithmetic tasks in financial contexts administered within the Clinical Dementia Rating in a sample of 100 PD patients. Patients were classified as cognitively normal (PD-NC) or mildly impaired (PD-MCI) according to Level I consensus criteria, and assessed using a neuropsychological test battery, neurological motor examination, and sociodemographic and clinical questionnaires. In total, 18% showed arithmetic deficits: they were predominately female, had longer disease duration, more impaired global cognition, but minor signs of depression compared to PD patients without arithmetic deficits. When correcting for clinical and sociodemographic confounders, greater impairments in attention and visuo-spatial/ constructional domains predicted occurrence of arithmetic deficits. The type of deficit did not seem to be arbitrary but seemed to involve impaired place × value processing frequently. Our results argue for the importance of further systematic investigations of arithmetic deficits in PD with sensitive tests to confirm the results of our exploratory study that a specific subgroup of PD patients present themselves with dyscalculia.